Temperament and character in patients with schizophrenia with a history of restraint - Margetić, Branimir (Array, 2013)
In order to increase the quality of treatment and improve safety on psychiatric wards, we should learn more about characteristics of patients who are at an increased risk of being mechanically restrained. The aim of the present study, conducted in forensic patients with schizophrenia, was to assess whether there is an association between temperament and character and the patients’ experience of being mechanically restrained. We recruited 56 male forensic patients with schizophrenia, without concomitant substance dependence and antisocial personality disorder, of whom 64% had experienced restraint. Patients were assessed by the Temperament and Character Inventory and the Positive and Negative Syndrome Scale. The analysis has suggested that higher levels of the novelty-seeking and more intensive psychotic symptoms may represent risk factors for the use of restraints. We conclude that certain personality characteristics may enhance the risk for the use of restraints. It is important to better understand the patients’ personality traits associated with such practice.